2019
DOI: 10.1016/j.hrthm.2019.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Outcomes with the EMBLEM S-ICD in Primary Prevention Patients with Low EF Study (UNTOUCHED): Clinical characteristics and perioperative results

Abstract: BACKGROUND The subcutaneous implantable cardioverterdefibrillator (S-ICD) has shown favorable outcomes in large registries with broad inclusion criteria. The cohorts reported had less heart disease and fewer comorbidities than standard ICD populations.OBJECTIVE The purpose of this study is to characterize acute performance for primary prevention patients with a left ventricular ejection fraction (LVEF) 35% (primary prevention 35%).METHODS Primary prevention 35% patients with no prior documented sustained ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…The S‐ICD appears well suited for patients with LVAD for several reasons. The S‐ICD is extravascular which likely explains the absence of reported bacteremia 1,3,4,6,7 which, in patients with LVAD, can be particularly life threatening. In addition, the prolonged duration from sensing to therapy delivery with the S‐ICD is ideal for patients with LVAD, where delayed therapy is preferred 8 …”
Section: Introductionmentioning
confidence: 99%
“…The S‐ICD appears well suited for patients with LVAD for several reasons. The S‐ICD is extravascular which likely explains the absence of reported bacteremia 1,3,4,6,7 which, in patients with LVAD, can be particularly life threatening. In addition, the prolonged duration from sensing to therapy delivery with the S‐ICD is ideal for patients with LVAD, where delayed therapy is preferred 8 …”
Section: Introductionmentioning
confidence: 99%
“…Another single centre study showed that the first shock during DFT was successful in just 75% and argues that DFT is still necessary for S-ICD implants [30]. However, these results do not comply with the first published studies about S-ICD safety, which showed a high conversion success rate of DFT during S-ICD implants, varying from 98.7-100% [31][32][33][34]. Tab.…”
Section: Omission Of Dft In S-icd Implantsmentioning
confidence: 88%
“…5 The American Heart Association guidelines 4 recommend sICDs for patients without proper venous access or at high risk of CDRIE. Boersma et al 56 reported low periprocedural complication rates, with 99.6% successfully implanted devices and high defibrillation efficacy (99.2% during defibrillation testing) among 1,116 patients who had undergone sICD implantation as primary prevention of SCD. In another study, Boersma et al 57 indicated a low risk of infection in sICD recipients, even in individuals with a history of CDRIE and explanted transvenous ICDs.…”
Section: Subcutaneous Cardioverter-defibrillatormentioning
confidence: 99%